Strength of Timbers: A Case Study in Cambodia - Chhouk ChhayHorng (Institut Teknologi Sepuluh Nopember, 2017)
This study investigates the strength properties of timbers which are mostly used in the construction field in Cambodia. About 46 species of timbers selected from 4 categories of woods are tested in the laboratory of Institute of Technology of Cambodia. The tests are done to measure the compressive strength parallel to the grain, compressive strength perpendicular to the grain, tensile strength perpendicular to the grain, bending strength and shear strength of each species of timbers. At the meantime, the unit weight, density, humidity and moisture contents of timbers are also measured. The results from the experiments are found that the unit weight of lumbers is very different from one species to another. It could be observed that as the density increases, the various strength properties also increase. Some timbers resist very well under the ground like PHCHEK (Shorea Obtusa), some others resist better in water than others, for example KOKI (Hopea Odorata). The outcome of the study could help students, researchers, construction companies and architects to design and construct wood construction projects more economically, safely and appropriately. The results of this study can be additionally useful for future research and shared with other researchers in different institutions within the region.